Formation and Development of Opera Art in Uzbekistan - Akbarovich, Rajabov Avaz (Research Parks Publishing LLC, 2023)
This article describes the emergence of opera art in Uzbekistan, in particular, the characteristics of the formation of Uzbek operas at the end of the 19th century and the beginning of the 20th century, based on the development of Uzbek national drama, musical drama, and also under the influence of foreign classical opera. There is talk about the mountain.